Parasitoids of Lobesia botrana (Lepidoptera: Tortricidae) in the Douro Demarcated Region vineyards and the prospects for enhancing conservation biological control. Issue 5 (6th October 2022) - Carlos, Cristina; Gonçalves, Fátima; Villemant, Claire; Paredes, Daniel; Salvação, Juliana; Torres, Laura
Abstract: The more restrictive regulations of pesticides in Europe have led to an increase in conservation biological control (CBC) research. However, little attention has been paid to the main determinants of Lobesia botrana parasitism. The Douro Demarcated Region landscape offers scope for the use of CBC. The study was conducted between 2002 and 2015 aiming at: (i) identifying parasitoids associated with L. botrana and evaluating their impact as biological control agents in each generation of the pest, and (ii) evaluating the effect of both the proportion of ecological infrastructures (EI) near the vineyards, and the impact of management practices (chemical treatments and ground cover) on the parasitism of L. botrana . A total of 3226 larvae/pupae of L. botrana were collected (15% were parasitized and 485 parasitoids emerged). A complex of 16 taxa of parasitoids was identified, the majority belonging to Hymenoptera. The most abundant were Elachertus sp. (Eulophidae), Campoplex capitator Aubert (Ichneumonidae), and Brachymeria tibialis (Walker) (Chalcididae), which represented 62.5, 12.6, and 12.0% of the total assemblage of parasitoids which emerged, respectively. The percentage of parasitism ranged from 0.0 to 61.5% (first generation), from 0.0 to 36.8% (second generation), and from 0.0 to 12.1% (third generation). Importantly, it was found that the parasitism rate was higher in vineyards with ground cover. In addition, EI in the area surrounding the vineyards produced a significant increase in parasitism. These results suggest potential for CBC of L. botrana if EI around vineyards, and ground cover with native perennial plants within vineyards, are encouraged.